Narasi Parenting Minato Kanae dalam Novel Penance: Indonesia - Putri Wulan Dari; Ferdinal (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
The aim of this study is to analyze the other side of parenting in Japan. Parenting is shown through two discourses, the influence of the family on the behavior and perceptions of children and differences in the living environment that can affect parenting patterns. Parenting discourse is expressed through qualitative research methods. The results obtained that parenting is not always applied well in family, for example the use of verbal and physical violence in moral teaching and demands for behavior. Meanwhile, differences in the living environment that affect parenting are shown through everyday life and the local community's perspective on education.